Efficacy of drug and endoscopic treatment of Crohn's disease strictures: A systematic review. Issue 2 (27th December 2020) - Schulberg, Julien D; Wright, Emily K; Holt, Bronte A; Wilding, Helen E; Hamilton, Amy L; Ross, Alyson L; Kamm, Michael A
Abstract: Background and Aims: Strictures are the commonest complication in Crohn's disease. Surgery and endoscopic dilation are the mainstays of treatment, while drug therapy has often been considered contraindicated. The benefit of nonsurgical treatments, particularly drug and endoscopic therapy, need to be defined. Methods: Ovid MEDLINE, Embase, Emcare, PsycINFO, CINAHL and the Cochrane Library (inception until August 30, 2019) were searched. Studies with ≥ 10 patients with Crohn's disease strictures, reporting on outcomes following medication or endoscopic treatment, were included. Results: Of 3480 records, 85 studies met inclusion criteria and formed the basis of this analysis. Twenty‐five studies assessed drug therapy; none were randomized trials. Despite study heterogeneity anti‐tumor necrosis factor (TNF) therapy appeared effective, with 50% of patients avoiding surgery after 4 years of follow up. No other drug therapy was of demonstrable benefit. Sixty studies assessed endoscopic therapy including 56 on endoscopic balloon dilation, two assessed needle knife stricturotomy, and two stent insertion. Dilation was equally effective for de novo and anastomotic strictures ≤ 5 cm in length, with most studies reporting a subsequent surgical rate of 30% to 50%. Repeat dilation was required in approximately half of all patients. Conclusions: Anti‐TNF drug therapy and endoscopic balloon dilation are effective strategies for avoiding surgery in patients with stricturing Crohn's disease. Additional endoscopic therapies require further evaluation. Early data suggest that combining these therapies may provide greater benefit than individual therapies. Optimization of current drug and endoscopic therapy, and the incorporation of newer therapies, are needed for stricturing Crohn's disease.